Risk and protection factors for different intensities of adolescent substance use: when does the Prevention Paradox apply? - Stockwell, Tim; Toumbourou, J.; Letcher, P.; Smart, D.; Sanson, A.; Bond, L. (Taylor and Francis, 2004)
The 'Prevention Paradox' applies when low-risk individuals in a population contribute the most cases of a condition or problem behaviour by virtue of their being in the majority, thereby recommending a universal or whole of population approach to prevention. The applicability of a universal as opposed to a targeted high-risk approach to the prevention of youth substance use was examined in two studies of children and adolescents conducted in Victoria, Australia. These studies were reanalysed by recombining developmental, social and individual measures to form cumulative risk indices for substance use. In Study 1, a crosssectional survey of students, most regular tobacco, alcohol and cannabis use by 15/16-year-olds occurred in the moderate and lowrisk groups, recommending a universal prevention strategy . However, the majority of illicit drug use occurred in the highest-risk group (top 15%). Furthermore, in younger age groups both legal and illegal drug use was concentrated mainly in the highest risk group. Study 2 used data from a major longitudinal study where risk factors at around age 11/12 years were used to predict substance use at age 17/18 years. Most students who admitted involvement in frequent smoking, heavy drinking and, although to a lesser degree, cannabis were classified as low or average risk. It is concluded that universal prevention strategies are needed for late adolescent alcohol, tobacco and cannabis use and more targeted strategies for addressing harm related to early age drug use, frequent cannabis use and illegal drug use.